The Impact of the Added Value of the Agricultural Sector on Economic Growth in Algeria: An Econometric Study for the Period (1993-2022) - Koridjidj , Benali (Finance and Business Economies Review, 2023)
This research aims to evaluate the impact of agricultural output on the rate of GDP in Algeria for the period 1993 to 2022, using the EViews.8 program, and to achieve the objective of the analysis, we adopted a selection of independent variables related to value Additives for agriculture, forestry and fishing sector, volume of agricultural raw materials exports and imports of raw materials The research found a positive correlation between the two variables evaluated, as an increase in the value-added of the agricultural sector by 1 unit leads to an increase in the level of GDP by 1.1012 units, so that the public authorities must implement active agricultural policies aimed at raising the level of non-oil revenues.